Kontribusi A.M Sangaji dalam Dunia Pendidikan (1892-1949) - Moh Yamin Rumra; Syah Awal; Abusalam Rery (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the contributions of A.M. Sangaji to the field of education during the period of 1922–1949 within the broader context of anti-colonial struggle. This research employs a qualitative method with a historical approach, involving the stages of heuristics, verification, interpretation, and historiography. Data sources are derived from library research, including books, scholarly articles, and relevant historical documents. The findings reveal that A.M. Sangaji’s contributions to education were closely intertwined with his political and social activism within Sarekat Islam. He actively established Qur’anic teaching centers and educational institutions, particularly in East Kalimantan, aimed at enhancing intellectual and religious awareness among indigenous communities. Furthermore, his role as a writer and orator significantly influenced the development of national consciousness and resistance against colonial rule. His integrity, ideas, and commitment to education highlight his substantial role in the history of Indonesian education. This study concludes that A.M. Sangaji’s contributions extended beyond formal education to encompass social, political, and religious education oriented toward the liberation of society from colonial oppression. Therefore, A.M. Sangaji deserves recognition as both an educational figure and a national hero, with enduring relevance for contemporary educational development.